2014
DOI: 10.3109/17453674.2013.878827
|View full text |Cite
|
Sign up to set email alerts
|

Cemented or uncemented hemiarthroplasty for the treatment of femoral neck fractures?

Abstract: Background and purposeCemented hemiarthroplasty is preferred in treating displaced fractures of the femoral neck in the elderly. The cementing process may cause a fat embolism, leading to serious complications or death. In this study, we wanted to determine whether use of uncemented hemiarthroplasty (HA) would lead to reduced mortality and whether there are differences in the complications associated with these different types of arthroplasty.Patients and methodsFrom the PERFECT database, which combines inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 23 publications
3
54
2
3
Order By: Relevance
“…Total hip replacement is associated with better functional outcomes than hemiarthroplasty, but complications, including blood loss are greater with total hip replacement surgery (Blomfeldt et al 2007). There is evidence that uncemented hemiarthroplasty leads to impaired mobility, induces more post-operative pain (Parker, Gurusamy & Azegami 2010, Li et al 2013, mechanical complications of the device (Yli-Kyyny et al 2014, Li et al 2013) and increased reoperation rates (Gjertsen et al 2012, Yli-Kyyny et al 2014 compared to cemented hemiarthroplasty. In contrast, a recent five-year followup study, randomized by surgical method after femoral neck fracture, reported better hip function measured by the Harris Hip Score for uncemented than for cemented hemiarthroplasty (Langslet et al 2013).…”
Section: Risk Factors For Hip Fracture 212mentioning
confidence: 99%
See 1 more Smart Citation
“…Total hip replacement is associated with better functional outcomes than hemiarthroplasty, but complications, including blood loss are greater with total hip replacement surgery (Blomfeldt et al 2007). There is evidence that uncemented hemiarthroplasty leads to impaired mobility, induces more post-operative pain (Parker, Gurusamy & Azegami 2010, Li et al 2013, mechanical complications of the device (Yli-Kyyny et al 2014, Li et al 2013) and increased reoperation rates (Gjertsen et al 2012, Yli-Kyyny et al 2014 compared to cemented hemiarthroplasty. In contrast, a recent five-year followup study, randomized by surgical method after femoral neck fracture, reported better hip function measured by the Harris Hip Score for uncemented than for cemented hemiarthroplasty (Langslet et al 2013).…”
Section: Risk Factors For Hip Fracture 212mentioning
confidence: 99%
“…Adequate mobility is required not only for participation in society but also to prevent more serious complications such as a second hip fracture or institutionalization and early mortality (Abrahamsen et al 2009, Gill et al 2013a, Leibson et al 2002. High age, pre-fracture mobility limitations, type of fracture, delayed surgery and surgical treatment are associated with mobility limitations and disability after hip fracture (Aktselis et al 2014, Gjertsen et al 2010, Stoen et al 2014, Yli-Kyyny et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Both cemented and uncemented hemiarthroplasty have provided good results. (1)(2)(3)(4)(5) Earlier studies reported a higher risk of DVT in cemented TKR and THR. (6)(7)(8)(9)(10) Several studies have also demonstrated thrombogenic properties of bone cement that may contribute towards the development of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Both cemented and uncemented hemiarthroplasty have been used with good results; recent literature shows that both techniques lead to good functional outcomes and postoperative pain control, although some authors reported that uncemented hemiarthroplasty was associated with more implant-related complications. (1)(2)(3)(4)(5) In earlier studies reported in the 1990s, the cemented prosthesis was associated with a higher incidence of deep vein thrombosis (DVT) in total knee replacements (TKR) and total hip replacements (THR). (6)(7)(8)(9)(10) Subsequent studies, however, provided contradictory results and there was a lack of new data thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of postoperative 7 and 30 day mortality were changed about 3.5% [21,23] and from 7.4% to 9.9% [3,11], respectively. In the current study, the postoperative rate of mortality was slightly higher than the literature.…”
Section: Wwwjceionlineorgmentioning
confidence: 99%